Anti-inflammatory effects of Vitex trifolia leaves hydroalcoholic extract against hydrogen peroxide (H2O2)- and lipopolysaccharide (LPS)-induced raw 264.7 cells - Ahmad Tamim Ghafari,; Aisyah Hasyila Jahidin,; Yuslina Zakaria,; Mizaton Hazizul Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Inflammation is the human body’s defensive response against harmful events and a hallmark of many chronic conditions. Commonly, pharmacological approaches to treat inflammation include the use of non-steroidal anti-inflammatory drugs (NSAIDs) that could potentially possess life-threatening side effects after prolonged use. Hence there is a need for safer alternatives with fewer possible side effects. Vitex trifolia is a shrub from the family Verbenaceae, which possesses potential anti-inflammatory effects and is traditionally used to treat inflammation-related diseases in several Asian countries. This study aimed to explore the antioxidant and anti-inflammatory effect of V. trifolia leaves hydroalcoholic extract (VT) against murine macrophages (RAW 264.7 cells) induced with hydrogen peroxide (H2O2) and lipopolysaccharide (LPS). The reactive oxygen species (ROS) production was evaluated in the H2O2-induced macrophages. On the other hand, the interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and cyclooxygenase (COX) levels were quantified in the LPS-induced macrophages. VT (25 & 50 μg/mL) showed protective effects and significantly (p<0.05) increased the cell viability and reduced the ROS production compared to that of macrophages treated with 300 μM H2O2 alone. Additionally, VT (50 & 100 μg/mL) significantly (p<0.05) reduced LPS-induced TNF-α and IL-6 levels and COX activity compared to the macrophages treated with LPS (1 μg/mL), alone. However, VT and diclofenac had no inhibitory effect on IL-1β induced by LPS. Moreover, a significant positive correlation was found between VT antioxidant and anti-inflammatory effects. Concisely, these outcomes showed the potential antioxidant and anti-inflammatory effect of VT with a positive correlation between these protective actions. Therefore, our results suggest that VT may serve as a source of nutraceutical compounds with impending antioxidant and anti-inflammatory activities. However, further molecular investigations on the isolated compounds of the plant and in vivo studies are suggested for future work.